Modern Risk Management Strategies: Framework Platforms to Minimize Disaster Threats in Eurasian Regions - N. Lukin, Vladimir; V. Matveev, Alexander; V. Musienko, Tamara; N. Chizhikov, Eduard; E. Aktersky, Yuri (International Journal of Engineering and Technology, 2018)
The main content and problems of implementing the Sendai Framework for Disaster Risk Reduction in the Eurasian geopolitical and geoeconomic space, and the formation of framework platforms in various Eurasian regions are actualized in the article. The legal and economic basics of the Russian platform are revealed through the example of the integrated security system in the Arctic zone of the Russian Federation. The place and role of the EMERCOM of Russia in implementing the Sendai Framework for Disaster Risk Reduction, its contribution to the development of indicators, and terminology related to disaster risk reduction are shown.Â Â Â